Climate Change and Range Expansion of Protostrongylid Nematodes in the Canadian Arctic - Kafle, Pratap (Graduate Studies, 2018)
Through this doctoral research, I aimed to determine the diversity, distribution and abundances of protostrongylids in muskoxen and caribou from several sites in Subarctic and Arctic Canada and investigate the northward range expansion of Umingmakstrongylus pallikuukensis and Varestrongylus eleguneniensis in relation to Arctic warming. I first developed morphological keys to differentiate the first stage larvae (L1) of U. pallikuukensis, V. eleguneniensis and Parelaphostrongylus andersoni. This enabled me to identify L1 to the species level and determine the intensity of infections. Secondly, I analyzed over 1600 muskox and caribou fecal samples, and 40 muskox lung samples to determine the diversity, distribution and abundance patterns of protostrongylids. I found that the diversity and abundance of protostrongylids varied geographically. Both U. pallikuukensis and V. eleguneniensis had expanded their ranges and increased in abundance on Victoria Island between 2013 and 2017, with U. pallikuukensis expanding its range faster than V. eleguneniensis. I also detected P. andersoni in the Dolphin and Union caribou herd. In the third part of the study, I determined the important life cycle parameters for U. pallikuukensis and V. eleguneniensis through lab experiments. I demonstrated that V. eleguneniensis has higher thermal requirements for larval development inside the intermediate host, a shorter prepatent and patent period, and lower fecundity than U. pallikuukensis. Based on these findings I hypothesized that higher thermal requirements and lower fecundity might be limiting the rate and extent of range expansion for V. eleguneniensis. Finally, to map the thermal niches of U. pallikuukensis and V. eleguneniensis from 1980 through to 2017, I parametrized a process-based mechanistic model (Degree-day model) using data derived from the lab experiments, the literature, and high-resolution temperature data from a regional climate model. Models indicated a substantial expansion in the zones of climatic suitability for ...